2015
DOI: 10.1136/jmedgenet-2015-103361
|View full text |Cite
|
Sign up to set email alerts
|

Fatal infantile mitochondrial encephalomyopathy, hypertrophic cardiomyopathy and optic atrophy associated with a homozygousOPA1mutation

Abstract: BackgroundInfantile-onset encephalopathy and hypertrophic cardiomyopathy caused by mitochondrial oxidative phosphorylation defects are genetically heterogeneous with defects involving both the mitochondrial and nuclear genomes.ObjectiveTo identify the causative genetic defect in two sisters presenting with lethal infantile encephalopathy, hypertrophic cardiomyopathy and optic atrophy.MethodsWe describe a comprehensive clinical, biochemical and molecular genetic investigation of two affected siblings from a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(65 citation statements)
references
References 24 publications
(29 reference statements)
1
62
1
Order By: Relevance
“…Although OPA1 is highly expressed in the retina, it is broadly expressed throughout the body and this might reflect the multiple disorders that have presented themselves in patients harboring heterozygous mutations of OPA1, including deafness and dementia (Carelli et al, 2015). Until recently, all OPA1 mutations found in patients have been identified as heterozygous, with the only homozygous OPA1 mutation causing early-onset encephalomyopathy, cardiomyopathy and death during infancy (Spiegel et al, 2016). In mice, homozygous Opa1 mutants die in utero, but heterozygous mutants reflect the main features of human ADOA, as well as additional phenotypes including cardiomyopathy (Alavi et al, 2007;Chen et al, 2012;Davies et al, 2007).…”
Section: Opa1 and Fusion Of The Inner Membranementioning
confidence: 99%
“…Although OPA1 is highly expressed in the retina, it is broadly expressed throughout the body and this might reflect the multiple disorders that have presented themselves in patients harboring heterozygous mutations of OPA1, including deafness and dementia (Carelli et al, 2015). Until recently, all OPA1 mutations found in patients have been identified as heterozygous, with the only homozygous OPA1 mutation causing early-onset encephalomyopathy, cardiomyopathy and death during infancy (Spiegel et al, 2016). In mice, homozygous Opa1 mutants die in utero, but heterozygous mutants reflect the main features of human ADOA, as well as additional phenotypes including cardiomyopathy (Alavi et al, 2007;Chen et al, 2012;Davies et al, 2007).…”
Section: Opa1 and Fusion Of The Inner Membranementioning
confidence: 99%
“…Remarkably, two Italian families carrying different OPA1 missense mutations have been reported with an atypical combination of parkinsonism, dementia and CPEO, but with only subclinical optic neuropathy [34]. More recently, a compound homozygous OPA1 mutation has been identified for the first time in two affected Jewish sisters from consanguineous parents who developed a fatal infantile encephalomyopathy with hypertrophic cardiomyopathy and optic atrophy [123]. However, instead of multiple mtDNA deletions, the muscle biopsy from one sister showed marked mtDNA depletion.…”
Section: Doa Plus Phenotypesmentioning
confidence: 99%
“…10 Severe syndromes affecting young children, due to recessive OPA1 inheritance, were also recently reported. 5,11,12 Although ADOA is an ubiquitous condition, [13][14][15][16][17][18] several studies have reported its possibly lower incidence in Asia. 19,20 Our aim was to investigate, for the first time, its occurrence in the multiethnic population of Singapore.…”
Section: Introductionmentioning
confidence: 99%